Health and social challenges of LGBT: Islamic perspective - Draman, Samsul; Hashi, Abdurezak Abdulahi (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
It is imperative that respective authorities, agencies and individuals address and heal these social illnesses by all curative means such as conventional and spiritual education, consultations and legislation. Like other types of social illnesses, LGBT and the behaviour of homosexuality must be duly tackled and corrected for the wellbeing of the nation and the ummah.